Modernization of Islam and Language Education in the Society 5.0 Era in the Perspective of Harun Nasution - Mahmudah, Mahmudah; Siregar, Maragustam; Putra, Wahyu Hanafi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to describe the thoughts of modernizing Islamic and language education in the Era Society; 5.0 Harun Nasution's perspective. This research is qualitative with a literature study approach. The research data is in the form of thoughts on the modernization of Islamic education in Indonesia from the perspective of Harun Nasution. Sources of data were obtained from several books by Harun Nasution. Data collection techniques with documentation. While data analysis with data reduction, data presentation, and conclusion. The research results show that first, the modernization of Islamic education is a historical necessity, and its movement can be initiated in Islamic universities. Second, to strengthen the contribution of Harun Nasution's thought in modernizing Islamic education, he recommended two major agendas of change, namely academic tradition and institutional transformation. In the academic tradition, he emphasizes curriculum changes that are more dynamic and futuristic, as well as a philosophical and critical methodology of Islamic studies. Islamic and language education curriculum to always be dynamic and futuristic in welcoming the Era of Society 5.0. Meanwhile, the intended institutional transformation is the change from IAIN to UIN. Harun Nasution's big agenda for modernizing Islamic education is considered strategic to lead Muslims to become modern and rational human beings without leaving faith and Islam.